2021
DOI: 10.3390/nu13030825
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Enablers and Barriers to Appropriate Infants and Young Child Feeding Practices in India: A Systematic Review

Abstract: Despite efforts to promote infant and young child feeding (IYCF) practices, there is no collective review of evidence on IYCF enablers and barriers in India. This review was conducted using 2015 Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) guidelines. Six computerized bibliographic databases, Scopus, PubMed, PsycINFO, CINAHL, Embase, and Ovid MEDLINE, were searched for published studies on factors associated with IYCF practices in India from 1 January 1993, to 30 April 2020. IYCF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 95 publications
1
10
0
Order By: Relevance
“…Although many of the trials have shown a positive association between maternal education and breastfeeding practices, there are some data suggesting maternal education to be negatively associated with exclusive breastfeeding. [ 32 ] In our study, we found it negatively associated with nighttime feeds. This may again be a region-specific finding.…”
Section: Discussionsupporting
confidence: 50%
“…Although many of the trials have shown a positive association between maternal education and breastfeeding practices, there are some data suggesting maternal education to be negatively associated with exclusive breastfeeding. [ 32 ] In our study, we found it negatively associated with nighttime feeds. This may again be a region-specific finding.…”
Section: Discussionsupporting
confidence: 50%
“…erefore, mothers who had higher household wealth had better ACFP compared to mothers who had lower household wealth. Other studies support this finding [42,43,[45][46][47]49]. Mothers who have higher household wealth are more likely to have food security for their babies.…”
Section: Discussionmentioning
confidence: 73%
“…erefore, the odds of ACFP increased, and mothers who had repeated ANC visits, repeated PNC visits, and institutional delivery had more ACFP than mothers who did not have these. Different studies also revealed that mothers who had repeated ANC visits, repeated PNC visits, and institutional delivery increased ACFP [41][42][43][45][46][47]. is might be because IYC feeding advice and counseling are components of ANC, PNC, and delivery services.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies in South Asia and West Africa also reported that the birth interval and birth order were associated with EIBF [ 19 , 22 ]. Findings from studies in Ethiopia and India also concluded that birth order and birth interval were among the predictors of EBF [ 23 , 24 ]. First-time mothers are less likely to use healthcare services regarding delivery and breastfeeding; therefore, the prevalence of EIBF and EBF was lower in this group.…”
Section: Discussionmentioning
confidence: 99%